A theory of school choice lotteries - Onur Kesten; M. Utku Ünver (Theoretical Economics, 2015)
A new mechanism was introduced in New York City and Boston to assign students to public schools. This mechanism was advocated for its superior fairness property, besides others. We introduce a new framework for school-choice problems and two notions of fairness in lottery design based on ex-ante stability. This framework unifies known many-to-one and one-sided matching models. We show that the NYC/Boston mechanism fails to satisfy these fairness properties. We then propose two new mechanisms, one that is ordinally Pareto-dominant within the class of strongly ex-ante stable mechanisms and one that satisfies ex-ante stability, equal treatment, and constrained ordinal-Pareto-efficiency.
Keywords: C71; C78; D71; D78; 330; Matching; school choice; deferred acceptance; stability; ordinal efficiency; market design